2017
DOI: 10.1111/ele.12814
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, tolerance and environmental transmission dynamics determine host extinction risk in a load‐dependent amphibian disease

Abstract: While disease-induced extinction is generally considered rare, a number of recently emerging infectious diseases with load-dependent pathology have led to extinction in wildlife populations. Transmission is a critical factor affecting disease-induced extinction, but the relative importance of transmission compared to load-dependent host resistance and tolerance is currently unknown. Using a combination of models and experiments on an amphibian species suffering extirpations from the fungal pathogen Batrachochy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 80 publications
0
69
1
5
Order By: Relevance
“…While theoretical models of Bd dynamics have explained the occurrence of low‐level Bd infections in host populations by assuming low rates of zoospore production (Briggs et al., ) and high levels of host resistance (Wilber et al., ), the effects demonstrated in our first experiment suggest that escape (Altizer et al., ) and recovery (Shaw & Binning, ) from infection during periods of terrestrial activity could also generate these patterns in semi‐terrestrial hosts. Accounting for periods that newts spend outside of aquatic habitat, our experiments generated infection patterns that were consistent with patterns in two populations of wild newts, emphasizing the ecological relevance of our experimental infections.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…While theoretical models of Bd dynamics have explained the occurrence of low‐level Bd infections in host populations by assuming low rates of zoospore production (Briggs et al., ) and high levels of host resistance (Wilber et al., ), the effects demonstrated in our first experiment suggest that escape (Altizer et al., ) and recovery (Shaw & Binning, ) from infection during periods of terrestrial activity could also generate these patterns in semi‐terrestrial hosts. Accounting for periods that newts spend outside of aquatic habitat, our experiments generated infection patterns that were consistent with patterns in two populations of wild newts, emphasizing the ecological relevance of our experimental infections.…”
Section: Discussionmentioning
confidence: 78%
“…In the case of newts, fully aquatic habitats are required for mating and offspring development. Since Bd ‐induced mortality appears to be a function of infection loads rather than infection status in various amphibian species (Stockwell, Clulow, & Mahony, ; Wilber et al., ), and since newts can reduce or even remove infections by switching to adjacent terrestrial habitat (as demonstrated in Experiment 1), the reproductive and energetic consequences of avoiding Bd exposure may be more costly than becoming infected. Given the conflicts that can arise from avoiding parasite exposure, and since most parasite infections do not deterministically lead to death, load‐dependent rather than risk‐dependent adjustments in routine habitat use may be an expected strategy for many wildlife species.…”
Section: Discussionmentioning
confidence: 99%
“…Total mortality and mortality rate were greater and the LD‐50 estimate lower in the North Carolina population compared to the Virginia population. Interestingly, the ID‐50 estimate for the Virginia population was lower than North Carolina, suggesting greater tolerance of the Virginia population to Bsal infection (Wilber, Knapp, Toothman, & Briggs, ). Variation in infection tolerance to amphibian pathogens among populations has been reported and could be related to differences in genetic diversity or local conditions that affected innate and adaptive immune defenses (Pearman & Garner, ; Savage & Zamudio, ).…”
Section: Discussionmentioning
confidence: 99%
“…), make identifying the factors that lead to extinction a conservation priority (Wilber et al. ). Geographic isolation of populations, host species community richness, variation in climate, and habitat differences across sites have all been suggested to influence amphibian– Bd dynamics (Searle et al.…”
Section: Introductionmentioning
confidence: 99%